Pengaruh Pemberian Ekstrak Putri Malu (Mimosa Pudica Linn) Terhadap Lama Penyimpanan Jamur Tiram (Pleuretus Ostreatus) - Maulida, Maulida (Medan Resource Center, 2023)
This study investigates the potential of Putri Malu (Mimosa pudica linn) extract, rich in saponins, as a natural preservative for oyster mushrooms (Pleurotus ostreatus) during storage. The objective is to determine the impact of the extract on the shelf life of the mushrooms and identify the optimal composition of the extract for maximum preservation. The experimental method is employed, utilizing a Completely Randomized Design (CRD) with four treatment groups of the Putri Malu extract. The results indicate a significant effect of the Putri Malu extract on prolonging the shelf life of oyster mushrooms. Among the different concentrations tested, the treatment using 176 ml of water combined with 24 ml of 12% Putri Malu extract (P4) exhibited the best preservation results. This study highlights the potential of natural preservatives derived from plants, specifically saponin-rich sources like Putri Malu, in extending the shelf life of perishable food items such as oyster mushrooms. The findings contribute to the development of eco-friendly preservation methods and promote the utilization of natural compounds for food preservation purposes.